(untitled) (Canadian Oncology Today, 2025)
Renal cell carcinoma (RCC) is the 10th most common cancer type in Canada. Numerous developments in the management of RCC over the last decade have led to improved outcomes, though these have mostly focused on the 80% of patients with clear cell renal cell carcinoma (ccRCC). The remaining 20% of cases are labelled non-clear cell renal cell carcinoma (non‑ccRCC) and represent a biologically and clinically heterogeneous group of diseases that are rare entities. Historically, non-ccRCC has been managed similarly to clear cell tumours. Localized non-ccRCC has better outcomes than ccRCC; however, survival of metastatic non-ccRCC is inferior to ccRCC (median overall survival [OS] of metastatic non-ccRCC reported as 39.2 months compared to 81.1 months for ccRCC). This has led to interest within the RCC scientific and patient communities to further improve outcomes for patients with non-ccRCC. This article describes the current management of patients with non-ccRCC and discusses future areas of interest in the field.